The Effect of Team Assisted Individualization (TAI) Learning Model on Student Mathematics Learning Outcomes - Roudhotul Janah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to know there is significant effect of using Team Assited Individualization (TAI) model on the mathematic students learning outcomes. The kind of the research is eksperimental research with quantitative approach. The subjects of the research are students of class VII A at SMP Satya Dharma Balung. With the data collecting method that used in the research are documentation, and test. The data analysis method that used is chi square. The value of chi square tes is 15,38 with dk is 1 and alpha 0,05 and chi square tabel is 3,841we know that chi square value > chi square table (15,38 > 3,841). So it is mean that Ha is approver and Ho is rejected, than we can say that there is significant effect of using team assited individualization (TAI) model on the mathematic students learning outcomes  Keywoard: team assited individualization, mathematic student learning outcomes